Management restructuring on distress firm in Indonesia - Ambarwati, Sri Dwi Ari; Haryono, ST (RSF Conference Series: Business, Management and Social Sciences, 2021)
Companies experiencing financial distress will try to solve these problems with various improvement efforts. One of the efforts that can be done is to carry out management restructuring, namely management changes. This study focuses on the management restructuring strategy on manufacturing companies that experience a decrease in performance, with the proportion of Earning Before Interest and Tax which decreased for two or more consecutive years period 2010 to 2020. The reason for taking this period is to capture the period after the 1997 crisis until the occurrence of global crisis in 2008. This study aims to examine the effect of ownership structure in choosing management turnover restructuring. The data used is cross-section data and processed using logistic regression with Stata. The results of this research simultaneously show that insider ownership, institutional ownership, family ownership, and corporate characteristic variables have an impact on the management restructuring decision. This study proves that the ownership structure mechanism affects the choice of management restructuring in distressed companies in Indonesia.